Subjective well-being of special needs children's mother in long-distance marriage - Izzatu Syarifah; Dewi Fitriana; Indah Andika Octavia (Faculty of Psychology, Universitas Negeri Yogyakarta, 2025)
This study aims to explore the subjective experiences of mothers in long-distance marriages (LDM) while raising a child with special needs, focusing on dimensions of subjective well-being (SWB) including life satisfaction, positive affect, and negative affect. Using qualitative methods with the Moustakas phenomenological approach, participants consisted of two primary subjects (mothers in long-distance marriages with a child with special needs) and four secondary subjects (close family members), selected using purposive sampling. Data were collected through in-depth interviews, observation, and document analysis, then analyzed through the stages of epoche , phenomenological reduction, imaginative variation, and meaning synthesis. The results showed that mothers experienced significant emotional challenges such as loneliness, stress, physical and mental exhaustion, and anxiety in parenting. However, sources of positive affect were also found in the form of family support, small successes in child development, and communication with partners. Determinants of subjective well-being (SWB) include self-acceptance, social support, and life experiences. This study emphasizes the importance of adequate emotional and social support to maintain mothers' subjective well-being in the context of long-distance marriage with children with special needs.